Hearing impairment in children - otolaryngologist's perspective, causes, diagnosis, rehabilitation and hearing prosthetics - Kamila Bała; Karolina Dorobisz (Termedia Publishing House, 2024)
Hearing impairment in children is a significant issue worldwide, including Poland, as it hinders their proper development. Early hearing prosthetics ensure language and social development comparable to their healthy peers. Proper diagnosis is essential to achieve this goal. In Poland, the Universal Newborn Hearing Screening Program allows for the rapid detection of children with hearing impairment and early therapeutic intervention. Bilateral sensorineural hearing loss is the primary indication for cochlear implantation. Patient assessment, surgery, and rehabilitation are carried out in highly specialized centers. Hearing impairment is also a concern for an older age group of children, where the causes are primarily inflammatory. In this case, parents, pediatricians, family doctors, speech therapists, and teachers play a significant role in suspecting hearing impairment in children. It is crucial to effectively and promptly include all children with hearing impairment in the program, especially those with risk factors, where delayed onset hearing loss may occur.